Learning English as a Foreign Language in Indonesia: Senior High School Students’ Motivation and Challenges - Missi Tri Astuti; Shalawati Shalawati; Sitti Hadijah (STAI Hubbulwathan Duri, 2022)
Investigation on English foreign language learners’ learning experiences has been discussed by a plethora of studies. The current study presents a survey on the learning motivation and challenges of Indonesian senior high school students. A cohort of approximately 64 students from a private senior high school in Indonesia was invited to participate in two questionnaires. Analysis of the students’ responses showed that their English language learning motivations were affected by both internal and external motivational factors, which were put into four categories; motivation for knowledge, internal fulfilment regulation, motivation to challenge, and external utility regulation. In terms of the challenges, boredom and anxiety were experienced by the students; although the degrees of the challenges were not significant, the students showed some factors that could trigger their anxiety and boredom. These findings suggest English language teachers keep stimulating the students to enhance and sustain their motivations in learning English both externally and internally and directing them to enjoy their learning process through innovative learning resources and activities.